A system dynamics model of employees’ performance - Alefari, Mudhafar; Almanei, Mohammed; Salonitis, Konstantinos (MDPI, 2020)
Employee performance is dynamic and can have great impact on the overall performance of any company and its sustainability. A number of factors that can be controlled by the company can affect the employees’ performance. The present paper starts with a thorough literature review for identifying these key driving in order to develop a system dynamics models that will be able to assess different improvement scenarios and initiatives. Based on causal loop diagrams, stock and flow diagrams are developed and solved using system dynamics theory. The model developed can be used for organizations to assess the impact of different improvement initiatives.
Keywords: modelling; manufacturing; system dynamics; employee performance